Method for harmless treatment of fermentation and squeezing waste solution of marigold - CHEN BAOSUN (2012)
The invention provides a method for harmless treatment of fermentation and squeezing waste solution of marigold, which comprises mixing the waste solution, biological bacteria and water absorption substances, and reacting under the action of the biological bacteria to obtain organic fertilizer, wherein the water content of the waste solution mixed with the water absorption substances is 40-70%; and the water absorption substances are composed of (by weight percentage) biomass 20-60, feces 10-40, and peat, lignite or fly ash 30-40. The invention harmlessly solves the problem of pollution of the fermentation and squeezing waste solution of marigold with high chemical oxygen demand (COD) and biochemical oxygen demand (BOD), and simultaneously utilizes a large amount of organic substances in the waste solution. The product can be used as fertilizer with good application effect, and has simple preparation method, easy operation, and industrial application.